2003
DOI: 10.1182/blood-2003-03-0850
|View full text |Cite
|
Sign up to set email alerts
|

Control of thrombus embolization and fibronectin internalization by integrin αIIbβ3 engagement of the fibrinogen γ chain

Abstract: Fibrin(ogen) deficiency (Fg -/-) was shown previously to be compatible with rapid thrombus growth within injured arterioles, but platelet fibronectin content was increased and newly formed thrombi were unstable. To further define the role of fibrin(ogen) in thrombus formation and stabilization, platelet biology was examined in mice expressing a form of fibrinogen that clots normally but lacks the ␥ chain C-terminal binding site for ␣IIb␤3 (Fg␥⌬5). Thrombus growth within the arterioles of Fg␥⌬5 mice appeared fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
96
2
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 83 publications
(100 citation statements)
references
References 36 publications
1
96
2
1
Order By: Relevance
“…4,21 Injury was induced by topical application of 30 L of 250 mM FeCl 3 , and the characteristics of thrombus formation were compared based on (1) number of fluorescent platelets deposited on the vessel wall during the first 3 to 5 minutes after injury, (2) time required for the formation of the first 20-m thrombus, and (3) time to complete vessel occlusion. 4,7,21,25 Cremaster arterial thrombosis model. To quantitatively study platelet accumulation within growing thrombi after the vascular injury in vivo, we used a laser to induce an arteriole thrombus in the cremaster muscle as previously described.…”
Section: Intravital Microscopy Thrombosis Modelsmentioning
confidence: 99%
“…4,21 Injury was induced by topical application of 30 L of 250 mM FeCl 3 , and the characteristics of thrombus formation were compared based on (1) number of fluorescent platelets deposited on the vessel wall during the first 3 to 5 minutes after injury, (2) time required for the formation of the first 20-m thrombus, and (3) time to complete vessel occlusion. 4,7,21,25 Cremaster arterial thrombosis model. To quantitatively study platelet accumulation within growing thrombi after the vascular injury in vivo, we used a laser to induce an arteriole thrombus in the cremaster muscle as previously described.…”
Section: Intravital Microscopy Thrombosis Modelsmentioning
confidence: 99%
“…2) [23,24]. While these results may have a simple explanation, resulting from the inhibition of fibrin formation by the anticoagulant, where fibrin contributes to thrombus stability under arterial shear rate [25], the emerging data indicate that the anti-thrombotic synergisms may originate from the complementation of the signaling pathways in platelets. Activation of the receptor function of GP IIb-IIIa is optimal when engagement of G 12/13 or G q signaling pathways is combined with G i stimulation [26,27].…”
Section: Combination Antithrombotic Therapymentioning
confidence: 99%
“…Furthermore, in vivo experiments where thrombus formation was induced with free radical-forming FeCl 3 allowed us to study the importance of this process in a thrombosis model known to rely on thrombin generation and coagulation. 16 The data showed that also in vivo the signaling cascade from GPVI to PLC␥2 led to coagulant activity and enhanced thrombus formation. …”
mentioning
confidence: 99%